A prediction model of mass transfer through an electrodialysis cell. Issue 47 (7th October 2016) - Ghorbani, Azadeh; Ghassemi, Abbas; Andersen, Paul K.; Foudazi, Reza
Abstract: The purpose of this work is to develop a mass transfer model that incorporates all relevant factors—migration, diffusion, and convection—to predict ion transfer in electrodialysis cells more completely than conventional models, which neglect convection. As a demonstration of this approach, the study develops a three-dimensional model that incorporates the factor of convection to predict NaCl mass transport through a rectangular electrodialysis cell. The equations used in the model—the complete Navier–Stokes, continuity, and steady-state Nernst–Planck equations—are solved by the finite difference numerical method in the particular control volumes. The equations in the dilute chamber are numerically solved using techniques from computational fluid dynamics (CFD). In order to evaluate the reliability and accuracy of the model, the results are compared with theory as calculated by the Nernst–Planck equation. We discovered that the developed model is capable of predicting the velocity distribution, separation percent, ion concentration distribution, and electrolyte potential in the chamber, with results that closely align with the theory. Additionally, by considering all three contributions, the developed model could predict a detailed distribution of concentration and potential drop in both the x - and y -directions.